Hypoglycemic agents and incidence of pancreatic cancer in diabetic patients: a meta-analysis - Zhao, Zimo; He, Xinyi; Sun, Yan (Frontiers in Pharmacology, 2023)
Hypoglycemic agents are the primary therapeutic approach for diabetes and have been postulated to impact pancreatic cancer (PC) incidence in diabetic patients. We conducted a meta-analysis to further evaluate and establish the associations between four common types of hypoglycemic agents (metformin, sulfonylureas, thiazolidinediones (TZDs), and insulin) and PC incidence in individuals with diabetes mellitus (DM).A comprehensive literature search of PubMed, Web of Science, Embase, and Cochrane Library identified studies that analyzed relationship between hypoglycemic agents and PC which were published between 2012 and September 2022. Randomized control trials (RCTs), cohorts, and case-control studies were included if there was clear and evaluated defined exposure to the involved hypoglycemic agents and reported PC outcomes in patients with DM. Also, there should be reported relative risks or odds ratios (OR) or other provided data for the calculation of OR. Summary OR estimates with 95% confidence interval (CI) were estimated using the random-effects model. Additionally, subgroup analysis was performed to figure out the source of heterogeneity. Sensitivity analysis and publication bias detection were also performed.11 studies were identified that evaluated one or more of the hypoglycemic agents, including 3 case-control studies and 8 cohort studies. Among these, 9 focused on metformin, 6 on sulfonylureas, 7 on TZDs, and 7 on insulin. Meta-analysis of the 11 observational studies reported no significant association between metformin (OR=1.04, 95% CI 0.73-1.46) or TZDs (OR=1.13, 95% CI 0.73-1.75) and PC incidence, while the risk of PC increases by 79% and 185% with sulfonylureas (OR=1.79, 95% CI 1.29-2.49) and insulin (OR=2.85, 95% CI 1.75-4.64) respectively. Considerable heterogeneity was observed among the studies and could not be fully accounted for by study design, region, or adjustment for other hypoglycemic agents.Sulfonylureas and insulin may increase the incidence of pancreatic cancer in diabetic patients, with varying effects observed among different ethnicities (Asian and Western). Due to significant heterogeneity across studies, further interpretation of the relationship between hypoglycemic agents and pancreatic cancer incidence in diabetic patients requires well-adjusted data and better-organized clinical trials.